Q-Switched And Mode-Locked Thulium Doped Fiber Lasers With Nickel Oxide Film Saturable Absorber - Harun, Sulaiman Wadi; Yasin, Moh; Ab Rahman, Mohd Fauzi; Abdul Latiff, Anas (Elsevier, 2019)
A passively Q-switched and mode-locked fiber laser based on thulium-doped fiber laser (TDFL) cavity was demonstrated utilizing nickel oxide (NiO) nanoparticles as a saturable absorber (SA). The NiO synthesis was carried out by using a facile sonochemical method and the prepared NiO thin film was sandwiched between two optical fiber ferrule connectors in the TDFL ring cavity. By controlling the loss and gain in the cavity, stable Q-switching operation was obtained. The repetition rate and pulse width were tunable from 6.71 kHz to 19.58 kHz and from 9.16